Investigations about periodic design for broadband increased sound transmission loss of sandwich panels using 3D-printed models. (February 2020) - Errico, F.; Ichchou, M.; De Rosa, S.; Franco, F.; Bareille, O.
Highlights: Tailoring of the structural elastic waves' propagation versus the acoustic one. Shifted and Folded walls core designs are proposed for sandwich complex structures. Broadband increased transmission loss keeping the mass of the system constant. Experimental verification of trends using 3D-printed panels with the designed cores. Abstract: Two types of sandwich panels are designed by using the periodic structure theory. A double-wall panel with mechanical links and a sandwich panel with rectangular core are studied. An oriented optimization of the elastic bending waves' propagation versus the acoustic wavenumbers is achieved by using shifted core walls and by keeping the mass and stiffness of the system constant. Standard and optimized configurations are 3D-printed and sound transmission measurements are carried out by using a facility with an uncoupled reverberant-anechoic configuration. The experimental evidences of enlarged bending band-gaps and deformation mechanisms are proved using a reverse approach based on the acoustic radiation of the panels.